2018
DOI: 10.1111/hepr.13233
|View full text |Cite
|
Sign up to set email alerts
|

Wisteria floribunda agglutinin‐positive Mac‐2 binding protein predicts early occurrence of hepatocellular carcinoma after sustained virologic response by direct‐acting antivirals for hepatitis C virus

Abstract: Post-SVR WFA -M2BP is a predictive factor for the development of HCC in patients with no previous HCC history and treated with DAAs. Post-SVR AFP was predictive for HCC recurrence after DAA therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 34 publications
4
44
0
Order By: Relevance
“…We have reported that MRE is useful for prediction of HCC development after SVR . Furthermore, the utility of serum fibrosis markers in the prediction of HCC development also has been reported . Therefore, we compared the accuracy of HCC development prediction by these markers in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have reported that MRE is useful for prediction of HCC development after SVR . Furthermore, the utility of serum fibrosis markers in the prediction of HCC development also has been reported . Therefore, we compared the accuracy of HCC development prediction by these markers in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The measurement of liver stiffness using magnetic resonance elastography (MRE) is a useful noninvasive method to diagnose liver fibrosis, and we have reported for the first time that MRE is useful for prediction of HCC development after SVR . Furthermore, usefulness of prediction of HCC development by various noninvasive serum fibrosis markers has been also reported . However, there is no report comparing these diagnostic accuracies for HCC development after SVR, and it is necessary to verify which noninvasive marker is useful for prediction of HCC development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar phenomena have been observed for other glyco‐biomarkers, such as fucosylated haptoglobin, suggesting that aberrant glycan alteration occurs in the early stages of hepatocarcinogenesis, and that such alterations might be useful biomarkers for diagnosis. Recent studies showed that M2BPGi is useful for the prediction of HCC development after sustained viral response by direct‐acting antivirals …”
Section: Glyco‐biomarkers For Liver Diseasesmentioning
confidence: 99%
“…Recent studies showed that M2BPGi is useful for the prediction of HCC development after sustained viral response by direct-acting antivirals. [30][31][32]…”
Section: Mac-2bpmentioning
confidence: 99%